Cost-effectiveness analysis comparing “PARP inhibitors-for-all” to the biomarker-directed use of PARP inhibitor maintenance therapy for newly diagnosed advanced stage ovarian cancer - Gonzalez, Rafael (Gynecol Oncol, 2020)
OBJECTIVES. Clinical trials evaluating universal PARP inhibitor (PARPi) frontline maintenance therapy for advanced stage ovarian cancer have reported progression-free survival (PFS) benefit. It is unclear whether PARPi maintenance therapy will universally enhance value (clinical benefits relative to cost of delivery). We compared a “PARPi-for-all” to a biomarker-directed frontline maintenance therapy approach as a value-based care strategy. METHODS. The cost of two frontline PARPi maintenance strategies, PARPi-for-all and biomarker-directed maintenance, was compared using modified Markov decision models simulating the study designs of the PRIMA, VELIA, and, PAOLA-1 trials. Outcomes of interest included overall costs and incremental cost-effectiveness ratios (ICERs) reported in US dollars per quality adjusted progression-free life-year (QA-PFY) gained. RESULTS. PARPi-for-all was more costly and provided greater PFS benefit than a biomarker-directed strategy for each trial. The mean cost per patient for the PARPi-for-all strategy was $166,269, $286,715, and $366,506 for the PRIMA, VELIA, and PAOLA-1 models, respectively. For the biomarker-directed strategy, the mean cost per patient was $98,188, $167,334, and $260,671 for the PRIMA, VELIA, and PAOLA-1 models. ICERs of PARPi-for-all compared to biomarker-directed maintenance were: $593,250/QA-PFY (PRIMA), $1,512,495/QA-PFY (VELIA), and $3,347,915/QA-PFY (PAOLA-1). At current drug pricing, there is no PFS improvement in a biomarker negative cohort that would make PARPi-for-all cost-effective compared to biomarker-directed maintenance. CONCLUSIONS. This study highlights the high costs of universal PARPi maintenance treatment, compared with a biomarker-directed PARPi strategy. Maintenance therapy in the front-line setting should be reserved for those with germline or somatic HRD mutations until the cost of therapy is significantly reduced.